Trichotillomania in Children − How can a Dermatologist Deal with it? - Sejal Thakkar; Nimisha Desai (Wolters Kluwer Medknow Publications, 2023)
Hair loss in children is an important cosmetic concern, especially in adolescents where body image matters. Trichotillomania manifests through patchy hair loss which reflects underlying psychiatric conditions. It is a challenge for the dermatologist, who are first contact physicians, to deal with such cases who are secretly struggling with their inner turmoil. Hence, they must be well versed to deal with such patients. The current review aims to facilitate the dermatologist to handle them effectively. We performed PubMed and Google Scholar searches of English literature using the terms "Trichotillomania", "Trichotillosis," "Trichotillomania in Children," "Trichotillomania in pediatrics," "Trichotillomania in adolescents," "Hair pulling disorder," "Obsessive-Compulsive disorders AND Dermatology," "Psychodermatology," and "Psychocutaneous disorders." The selected publications were reviewed for additional resources. Thorough psychological evaluation of the patient along with the cutaneous examination will help the dermatologists in establishing the diagnosis. Dermatologists should be empowered regarding the need of mental health referral and should be able to convey the same to the patient/family members empathetically. They can offer habit reversal therapy, mainstay treatment, as well as pharmacotherapy as and when needed after adequate training.